Pangenome-wide analysis of cyclic nucleotide-gated channel (CNGC) gene family in citrus Spp. Revealed their intraspecies diversity and potential roles in abiotic stress tolerance - Zia, Komal; Rao, Muhammad Junaid; Sadaqat, Muhammad; Azeem, Farrukh; Fatima, Kinza; Tahir ul Qamar, Muhammad; Alshammari, Abdulrahman; Alharbi, Metab (Frontiers in Genetics, 2022)
Cyclic nucleotide-gated channels (CNGC) gene family has been found to be involved in physiological processes including signaling pathways, environmental stresses, plant growth, and development. This gene family of non-selective cation channels is known to regulate the uptake of calcium and is reported in several plant species. The pangenome-wide studies enable researchers to understand the genetic diversity comprehensively; as a comparative analysis of multiple plant species or member of a species at once helps to better understand the evolutionary relationships and diversity present among them. In the current study, pangenome-wide analysis of the CNGC gene family has been performed on five Citrus species. As a result, a total of 32 genes in Citrus sinensis, 27 genes in Citrus recticulata, 30 genes in Citrus grandis, 31 genes in Atalantia buxfolia, and 30 genes in Poncirus trifoliata were identified. In addition, two unique genes CNGC13 and CNGC14 were identified, which may have potential roles. All the identified CNGC genes were unevenly distributed on 9 chromosomes except P. trifoliata had genes distributed on 7 chromosomes and were classified into four major groups and two sub-groups namely I, II, III, IV-A, and IV-B. Cyclic nucleotide binding (CNB) motif, calmodulin-binding motif (CaMB), and motif for IQ-domain were conserved in Citrus Spp. Intron exon structures of citrus species were not exactly as same as the gene structures of Arabidopsis. The majority of cis-regulatory elements (CREs) were light responsive and others include growth, development, and stress-related indicating potential roles of the CNGC gene family in these functions. Both segmental and tandem duplication were involved in the expansion of the CNGC gene family in Citrus Spp. The miRNAs are involved in the response of CsCNGC genes towards drought stress along with having regulatory association in the expression of these genes. Protein- Protein interaction (PPI) analysis also showed the interaction of CNGC proteins with other CNGCs which suggested their potential role in pathways regulating different biological processes. GO enrichment revealed that CNGC genes were involved in the transport of ions across membranes. Furthermore, tissue-specific expression patterns of leaves sample of C. sinensis were studied under drought stress. Out of 32 genes of C. sinensis 3 genes i.e., CsCNGC1.4, CsCNGC2.1, and CsCNGC4.2 were highly up-regulated, and only CsCNGC4.6 was highly down-regulated. The qRT-PCR analysis also showed that CNGC genes were highly expressed after treatment with drought stress, while gene expression was lower under controlled conditions. This work includes findings based on multiple genomes instead of one, therefore, this will provide more genomic information rather than single genome-based studies. These findings will serve as a basis for further functional insights into the CNGC gene family.